Respuesta :

#1

  • 2x²+x-6

ac=6(-2)=-12

  • 2x²+4x-3x-6
  • 2x(x+2)-3(x+2)
  • (2x-3)(x+2)

#2

  • 10a²+3a-1
  • 10a²+5a-2a-1
  • 5a(a+2)-1(a+2)
  • (5a-1)(a+2)

#3

  • 2c²+5c-12

ac=-24

  • 2c²+8c-3c-12
  • 2c(c+4)-3(c+4)
  • (2c-3)(c+4)

Answer:

(a)  [tex](2x-3)(x+2)[/tex]

(b)  [tex](5a-1)(2a+1)[/tex]

(c)  [tex](2c-3)(c+4)[/tex]

Step-by-step explanation:

To factor a quadratic in the form [tex]ax^2+bx+c[/tex]

  • Find 2 two numbers that multiply to ac and sum to b.
  • Rewrite b as the sum of these 2 numbers.
  • Factorize the first two terms and the last two terms separately, then factor out the common term.

Part (a)

Given expression:  [tex]2x^2+x-6[/tex]

[tex]\implies ac=2 \cdot -6=-12[/tex]

Factors of -12 that sum to 1:  4 and -3

[tex]\implies 2x^2+4x-3x-6[/tex]

Factor first two terms and last two terms separately:

[tex]\implies 2x(x+2)-3(x+2)[/tex]

Factor out common term [tex](x+2)[/tex]:

[tex]\implies (2x-3)(x+2)[/tex]

Part (b)

Given expression: [tex]10a^2+3a-1[/tex]

[tex]\implies ac=10 \cdot -1=-10[/tex]

Factors of -10 that sum to 3:  5 and -2

[tex]\implies 10a^2+5a-2a-1[/tex]

Factor first two terms and last two terms separately:

[tex]\implies 5a(2a+1)-1(2a+1)[/tex]

Factor out common term [tex](2a+1)[/tex]:

[tex]\implies (5a-1)(2a+1)[/tex]

Part (c)

Given expression: [tex]2c^2+5c-12[/tex]

[tex]\implies ac=2 \cdot -12=-24[/tex]

Factors of -24 that sum to 5: 8 and -3

[tex]\implies 2c^2+8c-3c-12[/tex]

Factor first two terms and last two terms separately:

[tex]\implies 2c(c+4)-3(c+4)[/tex]

Factor out common term [tex](c+4)[/tex]:

[tex]\implies (2c-3)(c+4)[/tex]